1965
DOI: 10.1042/bj0970247
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamins A and D on the biosynthesis of l-ascorbic acid by rat-liver microsomes

Abstract: 1. The synthesis of L-ascorbic acid from either D-glucuronolactone or L-gulonolactone by liver microsomes ofrats is decreased under conditions ofhypervitaminosis A; under hypervitaminosis D the synthesis from D-glucuronolactone is increased and that from L-gulonolactone is not affected. 2. The microsomal conversion of L-gulonolactone into L-ascorbic acid is impaired in liver tissues of rats made deficient with respect to either vitamin A or vitamin D when compared with the controls maintained on stock diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1968
1968
1998
1998

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Because ascorbic acid is synthesised in the yolk sac membrane during embryonic development (Yew, 1985) it is possible to suggest a regulating role for vitamin A in this process. For example, in rats excess vitamin A supplementation was associated with decreased ascorbic acid synthesis (Ghosh et al, 1965). On the other hand the effect may be indirect by changing the concentration of vitamin E which is considered to stimulate ascorbic acid synthesis in chicken tissues (Nagorna-Stasiak et al, 1997).…”
Section: Discussionmentioning
confidence: 98%
“…Because ascorbic acid is synthesised in the yolk sac membrane during embryonic development (Yew, 1985) it is possible to suggest a regulating role for vitamin A in this process. For example, in rats excess vitamin A supplementation was associated with decreased ascorbic acid synthesis (Ghosh et al, 1965). On the other hand the effect may be indirect by changing the concentration of vitamin E which is considered to stimulate ascorbic acid synthesis in chicken tissues (Nagorna-Stasiak et al, 1997).…”
Section: Discussionmentioning
confidence: 98%
“…Various workers have also reported a direct association between vitamin A deficiency and ascorbic acid synthesis. In 1965, Ghosh et al (31) reported that microsomal conversion of L-gulonolactone into L-ascorbic acid was impaired in the liver tissue of rats made deficient with respect to vitamin A. In our studies, we found that the protein status of the animals had a significant effect on the levels of vitamins A and C. As compared to the Std diet, in SHP there was a significant increase in the levels of vitamins A and C, while in the SLP diet there was a significant decrease in their levels.…”
Section: Discussionmentioning
confidence: 98%
“…Decreases in blood plasma ascorbic acid levels were reported to accompany vitamin A depletion of calves (Moore and Cotter, 1945) and chicks ). Malathi and Ganguly (1964) and Ghosh ^ (1967) have reported that activity of L-gulono-y-lactone oxidase is reduced in vitamin Adeficient rats. Rogers (1969), however, noted that the loss in enzymatic activity may be a result of reduced nutrient intake.…”
Section: Vitamin a By Ascorbic Acid Interactionmentioning
confidence: 99%